2019
DOI: 10.1002/pon.5262
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the unmet supportive care needs of men on active surveillance for prostate cancer

Abstract: Objective Understanding the unmet supportive care needs of men on active surveillance for prostate cancer may enable researchers and health professionals to better support men and prevent discontinuation when there is no evidence of disease progression. This review aimed to identify the specific unmet supportive care needs of men on active surveillance. Methods A systematic review following PRISMA guidelines was conducted. Databases (Pubmed, Embase, PsycINFO, and CINAHL) were searched to identify qualitative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 61 publications
1
31
1
Order By: Relevance
“…This might be comparable to patients on watchful waiting (e.g. prostate or lymphoma patients) (McIntosh et al, 2019) or those living with 'chronic metastatic disease' (Kida et al, 2021). Nevertheless, scores for EHE patients who are undergoing treatment may also be relatively lower than expected since these patients are more likely to have more frequent hospital visits and therefore easier access to supportive care.…”
Section: Sociodemographic and Clinical Characteristics Associated With Supportive Care Needsmentioning
confidence: 93%
“…This might be comparable to patients on watchful waiting (e.g. prostate or lymphoma patients) (McIntosh et al, 2019) or those living with 'chronic metastatic disease' (Kida et al, 2021). Nevertheless, scores for EHE patients who are undergoing treatment may also be relatively lower than expected since these patients are more likely to have more frequent hospital visits and therefore easier access to supportive care.…”
Section: Sociodemographic and Clinical Characteristics Associated With Supportive Care Needsmentioning
confidence: 93%
“…Overdiagnosis turns healthy men into patients which may take its toll on psychological well-being and quality-of-life. 35,36 Most importantly, over the past two decades, most men with low risk prostate cancer in the US underwent treatment with surgery and radiation. Such overtreatment has no, or almost no, benefit in terms of mortality reduction but leads to important and persistent side-effects, most notably, urinary and erectile dysfunction.…”
Section: Current Evidence For Prostate Cancer Screeningmentioning
confidence: 99%
“…Literature on PC survivors covers diverse topics, such as available psychosocial interventions or unmet supportive care needs while undergoing specific treatments (Holm et al, 2018;McIntosh et al, 2019;Parahoo et al, 2013). A systematic review and qualitative synthesis by King et al (2015) explored men's experiences of and needs for supportive care, and reported that more patient-centred, nurse-led supportive care is required.…”
Section: Introductionmentioning
confidence: 99%